Casa do Artesão e o fomento da produção artesanal mato-grossense : a criação e difusão de bens simbólicos para a construção de uma identidade regional (1975-2018) - Torres, Anderson Pinheiro (2021)
Through this dissertation, we intend to analyze the construction and diffusion of symbolic cultural goods of material and immaterial origin to create a regional identity in Mato Grosso and the importance that the project of the government of the state of Mato Grosso, aimed at social promotion entitled Casa do Artesão had in that sense. In this way, we will analyze its role in the promotion of cultural tourism in the state of Mato Grosso, and how the discourse based on the valorization, above all, of the crafts and knowledge of the popular strata, through its commercialization, was engendered. Thus, the period from 1975 to 2018 was considered, due to the transformation of the building that is no longer a school, being transformed at the initiative of the state government into a space aimed at the dissemination of regional culture and the sale of local handicrafts. With this, this dissertation aims to establish an analysis about material and immaterial culture, and how over time a regional Mato Grosso identity was being built and consolidated and how the artisanal production of the state of Mato Grosso ended up being submitted to market demands, having Casa do Artesão in Cuiabá as object of analysis and the relationship established between it and the handicrafts produced in the state. Thus, we seek to discuss over time the appropriation of certain elements that come to constitute a new regional identity, as well as the transformations undergone in space, which in turn leads us to a reinvention of the space itself, its institutionalization and consequent spectacularization of popular culture, transforming it into a salable product, under the discourse of social promotion and incentive to artisanal production and perpetuation of the knowledge of the popular layers